Determinants of early pospartum psychological reaction among mothers in Kuala Lumpur Hospital - Musa, Ramli; AAW, Abdullah; MIB, Saiful; MN, Hafiz; AAZ, Fahmi (Faculty of Medicine, International Islamic University Malaysia, 2010)
Introduction: Maternal psychological well-being determines early mother-infant relationship and baby’s health. Paying attention on this aspect is essential particularly in early postpartum period. This study aimed to determine early psychological reactions toward socioeconomic profi les, delivery methods and delivery outcomes among postpartum mothers in Kuala Lumpur Hospital. Materials and Methods: A total of 150 twoweek- postpartum mothers participated in this cross sectional study and their psychological perspective was measured by using the Depressive, Anxiety and Stress Scale (DASS). Results: 4%, 16% and 4.7% of respondents had signifi cant depressive, anxiety and stress levels respectively. Conclusion: Socioeconomic variables such household income, level of education and presence of medical illness were statistically signifi cant to determine early postpartum psychological reactions but not the modes or outcomes of delivery.